Vortioxetine Improves Context Discrimination in Mice Through a Neurogenesis Independent Mechanism - Felice, Daniela; Guilloux, Jean-Philippe; Pehrson, Alan; Li, Yan; Mendez-David, Indira; Gardier, Alain M.; Sanchez, Connie; David, Denis J. (Frontiers in Pharmacology, 2018)
Major Depressive Disorders (MDD) patients may exhibit cognitive deficits and it is currently unclear to which degree treatment with antidepressants may affect cognitive function. Preclinical and clinical observations showed that vortioxetine (VORT-, an antidepressant with multimodal activity), presents beneficial effects on aspects of cognitive function. In addition, VORT treatment increases adult hippocampal neurogenesis (AHN) in rodents, a candidate mechanism for antidepressant activity. Pattern separation (PS) is the ability to discriminate between two similar contexts/events generating two distinct and non-overlapping representations. Impaired PS may lead to overgeneralization and anxiety disorders. If PS impairments were described in depressed patients, the consequences of antidepressant treatment on context discrimination (CD) are still in its infancy. We hypothesized that VORT-increased adult hippocampal neurogenesis may improve CD. Thus, in an attempt to elucidate the molecular mechanism underpinning VORT treatment effects on CD, a rodent model of PS, the role of adult hippocampal neurogenesis and stress-induced c-Fos activation was evaluated in the adult mouse hippocampus. Chronic treatment with VORT (1.8 g/kg of food weight; corresponding to a daily dose of 10 mg/kg, 3 weeks) improved CD in mice. Interestingly, chronic treatment with VORT reversed ablation of AHN-induced delay in CD and freezing behaviour. VORT treatment decreased stress-induced c-Fos activation in the dorsal but not ventral dentate gyrus. VORT treatment did not affect c-Fos activity in the hippocampus of mice with ablated neurogenesis. This study highlights a role of VORT in CD, which may be independent from AHN and hippocampal c-Fos activation. Further studies elucidating the mechanisms underlying VORT’s effects in CD could contribute to future strategies for alleviating the disease burden for individuals suffering from depression and/or anxiety disorders.